Gadget Use and Speech Delay Risk in Toddlers: Penggunaan Gadget dan Risiko Speech Delay pada Anak Toddler - Umriana, Anila; Indanah, Indanah; Yulisetyaningrum, Yulisetyaningrum (Indonesian Journal of Innovation Studies, 2026)
General Background: Early childhood is a critical period for language acquisition, during which speech delay may disrupt communication and social development. Specific Background: The increasing prevalence of gadget use among children aged 18–36 months has raised concerns regarding reduced verbal interaction and language stimulation, particularly within community-based health services such as Posyandu. Knowledge Gap: Although gadget exposure in early childhood continues to rise, localized empirical evidence examining its association with speech delay risk remains limited. Aims: This study aimed to analyze the relationship between gadget use and the risk of speech delay among children aged 18–36 months at the Posyandu of Jetiskapuan Village, Jati District, Kudus Regency. Results: A quantitative correlational study with a total sample of 58 children was conducted using a gadget use questionnaire and the Indonesian version of the Receptive Expressive Emergent Language Scale, with data analyzed through Spearman Rank correlation. The findings demonstrated a strong and statistically significant negative relationship between gadget use and children’s language ability (r = −0.668; p < 0.001), indicating that higher levels of gadget use were associated with greater risk of speech delay. Novelty: This study provides community-based evidence highlighting the strength and direction of the association between gadget use intensity and speech delay risk in toddlers. Implications: The findings underscore the importance of parental supervision of gadget use and active verbal stimulation to support optimal language development during early childhood. Highlights • Higher levels of gadget use were associated with lower language ability scores in children aged 18–36 months.• Receptive language abilities were more developed than expressive language abilities among the participants.• Gadget use was predominantly passive, with limited interactive communication activities. Keywords Gadget Use; Speech Delay; Early Childhood; Language Development; Posyandu